URGENSI MANAJEMEN DALAM DA’WAH: Konsep Pengembangan dan Ruang Lingkup Pembahasannya - Imam Taufik Alkhotob (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2020)
Da'wah activities require regular steps in achieving goals. The various challenges in da'wah cannot be faced sporadically or simply follow the direction of the flow of water. It takes proper efforts to achieve da'wah goals, so that the da'wah can achieve effectiveness and efficiency. For this reason, an answer is needed about the question of how to make this da'wah run well. The answer is the strength of the dakwah management. This research will explain how management knowledge is needed in da'wah. Through a qualitative approach method and literature study, the author will describe the scope of da'wah management needed in achieving da'wah goals, namely; At Takhtith / Planning (Planning), Tanzhim / Organizing, Taujih / Akcutating / Motivating (Direction / Action), and Riqabah / Controling (Supervision). Each with its own techniques and approaches.